Polityka edukacyjna i językowa krajów afrykańskich (na przykładzie Senegalu) - NDiaye, Iwona Anna; NDiaye, Bara (Papers in Linguistics, 2020)
The article investigates a complex language situation and education problems using the example of Senegal, a small country in West Africa, its language varieties and cultural mix resulting from the influence of three major civilizations meeting at the country’s territory: Black African, Arabo-islamic and West-French.